Numerical simulation of earth fissures due to groundwater withdrawal - Z. Wang; Y. Zhang; J. Wu; J. Yu; X. Gong (Proceedings of the International Association of Hydrological Sciences, 2015)
Excessive groundwater withdrawal can cause land subsidence and earth fissures. The initiation and propagation of earth fissures are related to tensile failure and crack propagation in soils. Based on fracture mechanics, the crack band model (CBM), one of the smear crack models which is relatively easy to construct and convenient to be integrated into standard finite element codes is used in this paper. The calculated results of CBM are less dependent on the sizes of finite elements. The model was applied to simulate the formation and propagation of earth fissures in the hydrostratigraphic units with a bedrock ridge. The simulated positions and patterns of earth fissures coincide with field observations, suggesting that the modeling approach is adept to simulate the initiation and propagation of earth fissures due to groundwater withdrawal.